1992
DOI: 10.1099/00221287-138-2-337
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a circular plasmid from the yeast Kluyveromyces waltii

Abstract: A new plasmid was found in the yeast Kluyoeromyces wdtii. This high-copy-number plasmid, named pKW1, is a double-stranded circular DNA plasmid of 5619 bp. It has several features characteristic of the 2ptype plasmids: presence of two inverted repeats and four open reading frames, as well as the interconversion of two isomeric forms. However, the nucleotide sequence shows little homology with known yeast plasmids. An ARS function was localized within a segment of 545 bp near one of the inverted repeats. Chimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Only reads mapping uniquely in the L. waltii genome were analyzed. The L. waltii genome used here includes the assembled L. waltii genome described previously (Di Rienzi et al 2011), the L. waltii mating locus, the 2 mm plasmid (Chen et al 1992), and the rDNA locus (described here; see Supplemental Text). For aligning paired-end reads, an insert size between 250 and 1100 was allowed in Bowtie.…”
Section: Illumina Sequence Data Analysismentioning
confidence: 99%
“…Only reads mapping uniquely in the L. waltii genome were analyzed. The L. waltii genome used here includes the assembled L. waltii genome described previously (Di Rienzi et al 2011), the L. waltii mating locus, the 2 mm plasmid (Chen et al 1992), and the rDNA locus (described here; see Supplemental Text). For aligning paired-end reads, an insert size between 250 and 1100 was allowed in Bowtie.…”
Section: Illumina Sequence Data Analysismentioning
confidence: 99%
“…[9]. Our results show that the Kw protein is alone sufficient to promote intermolecular and intramolecular recombination in vitro of a DNA target site consisting of two 18-bp elements separted by a 7-bp spacer.…”
mentioning
confidence: 68%
“…The 2 p-like plasmid, pKWl from K. waltii contains four ORF A, B, C and D. Chen et al [9] suggested that the A gene encodes a recombinase, on the basis of similarity of its deduced amino acid sequence with that of the FLP gene of 2 p and its equivalent in other yeast plasmids. Like other 2 p plasmids, pKWl has two inverted repeat sequences of about 300 bp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations